The secularization of medical-hospital assistance at praia de Santa Luzia: representations of the sisters of charity and their role in the santa casa de misericordia of the court (Ágora Journal, 2026)
This article analyzes the discussions surrounding medical-hospital assistance at the Santa Casa de Misericórdia of Rio de Janeiro under the care of the Sisters of Charity, beginning in the 1850s. Their work was challenged by the Faculty of Medicine of the Court due to their interference in the recommended prophylactic measures for treating the sick. A conflict is evident between the religious and medical-scientific perspectives in health care. This tension intensified with the emerging dispute over the female body from within the practices of obstetrics and gynecology clinics. The process of secularization and ultramontanism during the Second Reign is considered essential for understanding the discrediting representations of the Sisters of Charity in the press.
Keywords: Santa Casa; assistance; faculty of medicine; secularization; imperial politics.